Pengaruh Modal, Nilai Produksi dan Tingkat Upah terhadap Penyerapan Tenaga Kerja Industri Kecil di Kabupaten Sidoarjo - Ghazy Guwairy, Alphard; Galih Wicaksono, Amirul; Tiana Rose, Neni; Marta Safitri, Tiara; Oktavina Radianto, Denny (VISA: Journal of Vision and Ideas, 2023)
This study was conducted to analyze the factors that influence employment in the Small Industry Sector in Sidoarjo Regency. Through the results of this study, it is expected to contribute to the scientific field, especially in business management related to employment in the small industry sector. The population of this study includes all small industries in Sidoarjo Regency. The results showed that capital has no influence on employment in the small industry sector in Sidoarjo Regency. However, production value has a significant positive effect on labor absorption in the small industry sector in Sidoarjo Regency. This means that the demand for labor by entrepreneurs is influenced by the number of goods produced by these workers. In addition, the wage level also has a significant negative effect on employment in the small industry sector in Sidoarjo Regency. This means that the higher the wage level, the lower the demand for labor by employers. Keywords: capital, production value, wages, labor